Wilson Disease in Children: Diagnosis and Management Update (KYAMC Journal, 2021)
Wilson disease is an autosomal recessive, copper storage disease, caused by a mutation in the ATP7B gene. Due to mutation in ATP7B is decreased secretion of ceruloplasmin into blood and decrease in excretion of copper into bile. Excess copper accumulate to toxic levels,mainly in the liver and secondarily in other organs. Children clinically become symptomatic after the age of 5 years. Clinical features ranges from asymptomatic raised transaminases to variable degree of liver disease, neurological symptoms and according involvement of other oragns. Diagnosis of Wilson disease is challenging. Modified Leip-zig score is useful for diagnosis. Treatment can be done with zinc and other chelators.KYAMC Journal Vol. 11, No.-4, January 2021, Page 212-217